Is it possible to resterilize disposable laparoscopy trocars in a hospital setting? - (:unkn) unknown (Lippincott Williams and Wilkins, 2000)
Nosocomial infections associated with interventional procedures have been attributed to improper decontamination of instruments. Disinfection of solid laparoscopic instruments, such as telescopes, by 2% glutaraldehyde and ethylene oxide was shown to be effective in preventing infection transmission. However, instrument design in more complex surgical instruments may hamper the quality of disinfection. The aim of this study is to investigate the safety of hospital disinfection of disposable laparoscopic instruments with a relatively more complex design. A total of 40 laparoscopic trocars were divided into two equal groups: group 1 was contaminated with bacteria and yeast, and group 2 was contaminated with the hepatitis B virus. Each group was then divided to two equal subgroups. After disinfecting subgroup A with 2% glutaraldehyde and B with ethylene oxide, samples were obtained for bacterial cultures and for virus detection using polymerase chain reaction (PCR). Bacterial and yeast cultures were positive in three instruments in group 1A and in two instruments in group 1B. Tests results for the hepatitis B virus were negative in group 2A, but positive in group 2B. Results of this study indicate that disinfection for multiple use of disposable laparoscopic instruments with a relatively complex structure is not effective and may result in nosocomial disease transmission by bacteria, fungi, and viruses.
Keywords: Disposable; Ethylene oxide; Glutaraldehyde; Hepatitis B; Polymerase chain reaction; Sterilization